The Effect of Problem-Based Learning Supported by Augmented Reality and Learning Motivation on the Critical Thinking Skills of Elementary School Students - Nur Dani Rumanti; Kartika Chrysti; Sudiyanto Sudiyanto (Journal of Educational Sciences, 2026)
This study aims to analyze the effect of the Problem-Based Learning (PBL) model supported by Augmented Reality on critical thinking skills. Critical thinking skills are an important variable because they are related to the ability to think reflectively and rationally. PBL was chosen because it encourages students to analyze problems and evaluate information. The study employed a quantitative approach with a one-group pretest-posttest design involving 58 fourth-grade students in the Gajah Mada Cluster on the topic of the solar system. The research instrument consisted of a critical thinking skills test developed based on Ennis’s indicators. Data were analyzed using descriptive and inferential statistics through paired t-tests and N-Gain tests. The results showed an improvement in critical thinking skills, indicated by an increase in the average score from the pretest to the posttest, as well as a statistically significant difference (sig. < 0.05). The N-Gain value of 0.53 falls into the moderate category, indicating that the learning process had a sufficiently effective impact. This improvement was supported by students’ active engagement in critical thinking and concrete visualization through Augmented Reality, which aided the analysis and reasoning processes. Thus, Problem-Based Learning supported by Augmented Reality is effective in improving the critical thinking skills of elementary school students.